Water scarcity and population displacement in southern Iraq: Perceptions and reality - Fatli, Tiba (AUC Knowledge Fountain, 2018)
This thesis argues that water scarcity causes significant displacement in Iraq’s southern region. It makes two related sub-points. First, in addition to local factors, international and transnational factors contribute to water scarcity and attendant displacement in Southern Iraq. Second, the stakeholders – whether displaced populations, local government officials, federal policy makers, non-governmental organizations or international development organizations – focus on particular factors of water scarcity rather than addressing the causes holistically. In general, researchers and policy-makers underestimate or neglect water-related causes of displacement, not only in Iraq but globally. Even when addressed, emphasis is placed on local and national causes, without contextualizing the relationship between internal and external factors. This thesis asks for more attention to be paid to how national, international, and transnational factors operate alongside and in relation to each other. Effective policies also need to understand how displaced persons perceive these factors because their lived experiences often differ from institutionalized international narratives on resource management. Ultimately, policy-making will be more effective at all levels by better understanding the water-related reasons for displacement in the national, international, and transnational contexts in an interrelated way.